6th Annual Vancouver Folk Music Festival - Vancouver Folk Music Festival Societyet al (1983)
Jericho Beach Park 6TH ANNUAL Vancouver Folk Music Festival/ A Capella [sic] - African - Australian - Black American - Bluegrass - Blues - British - Country & Western - Dancing - Eastern European Feminist - Greek - Hot Pickin' - Irish - Latin American - Newfoundland - Old Timey - Quebecois - Songwriting - Storytelling - Swedish/ July 15, 16, 17, 1983 Jericho Beach Park - Mainstage Concerts Each Evening - 5 Daytime Workshop Stages Sat. & Sun. - Crafts - Children's Programming - Food/ Who's Coming: Peter Alsop - Frankie Armstrong - Roy Bailey Anita Best - Pierre Bensusan Bim - Heather Bishop - Blowzabella The Blueflame Stringband - Eric Bogle & John Munro Pam & Phil Boulding - Bryan Bowers Rodney Brown & Mel Brown - Bob Brozman - Jo Carson Charged Particles - Comhaltas Ceoltoiri Eireann Steve Cormier - Barbara Dane - The Alex Eppler Group Eritage - David Essig - Vasilios Gaitanos - Terry Garthwaite The Golden Eagles - Stefan Grossman - Grupo Aymara Gerry Hallom - Caitlin Hanford & Chris Whiteley Bobbie Louise Hawkins - Connie Kaldor - Kin Lalat Richard LePage - Limited Edition & Denis LePage Magpie - Messi Martin & Los Camaroes - Memphis Slim Lydia Mendoza - Frazier Moss & Justin Demts J.P. Nystroms - Geoff Panting - Faith Petric Frankie & Doug Quimby - John Renbourn - Riders in the Sky Jean Ritchie - Anne Romaine - Leon Rosselson - Sparky Rucker Kelly Russell, Rufus Guinchard & Jim Payne Sabia - Jane Sapp - Gino Clay Sky - Skyline Len Snow - Rosalie Sorrels - Orrin Star & Gary Mehalick Sukay - Dave Swarbrick & Simon Nicol Sweet Honey in the Rock - Richard Thompson The Twelve Moon Storeytellers The Vancouver Morris Men - Pop Wagner Nancy White & Doug Wilde - Ken Whiteley Nimrod Workman - Zenska Pesna/ With the assistance of the TOURING OFFICE of the Canada Council/ Sponsored by the Vancouver Folk Music Festival Society with assistance from the City of Vancouver; Vancouver Board of Parks & Recreation; The Heritage Festival Society; the Province of British Columbia Cultural Services Branch; The Provincial Ministry of Labour; and the Department of Employment & Immigration. Thanks, Folks!/ Admission prices; Early Bird Special (until June 18) .00 Advance Weekend Tickets (after June 18) .00 Weekend Tickets at the Gate .00 Friday night .00 Saturday & Sunday ea. .00 Children under 12 accompanied by adult, and O.A.P. FREE/ Tickets available in Vancouver at all VTC & CBO ticket outlets (687-1818); at Black Swan Records, 2936 W. 4th (734-2828), and Octopus Books, 1146 Commercial Dr. (253-0931); in Victoria at Richards Records, 1318 Government St. (383-2733) and Victoria Folklore Centre, 539 Pandora Ave. (383-3412). Further information and tickets including mail orders from Vancouver Folk Music Festival, 3271 Main Street, Vancouver, B.C. V5V 3M6. Telephone (604) 879-2931.